Harmane Potentiates Nicotine Reinforcement Through MAO-A Inhibition at the Dose Related to Cigarette Smoking - Ding, Zheng; Li, Xiangyu; Chen, Huan; Hou, Hongwei; Hu, Qingyuan (Frontiers in Molecular Neuroscience, 2022)
Nicotine is the primary addictive component in cigarette smoke, and dopamine release induced by nicotine is considered a significant cause of persistent smoking and nicotine dependence. However, the effects of nicotine replacement therapy on smoking cessation were less effective than expected, suggesting that other non-nicotine constituents may potentiate the reinforcing effects of nicotine. Harmane is a potent, selective monoamine oxidase A (MAO-A) inhibitor found in cigarette smoke, but showed no effect on nicotine self-administration in previous studies, possibly due to the surprisingly high doses used. In the present study, we found that harmane potentiated nicotine self-administration on the fixed ration schedule at the dose related to human cigarette smoking by the synergistic effects in up-regulating genes in addiction-related pathways, and the effect was reduced at doses 10 times higher or lower than the smoking-related dose. The smoking-related dose of harmane also enhanced the increase of locomotor activity induced by nicotine, accompanied by increased dopamine basal level and dopamine release in the nucleus accumbens through MAO-A inhibition. Our findings provided new evidence for the important role of non-nicotine ingredients of tobacco products in smoking addiction.